NEXUS BETWEEN INTERNATIONAL TRADE AND FINANCIAL DEPTH IN NIGERIA - Opara, Godstime Ikechukwu (African Journal of Social and Behavioural Sciences, 2023)
This study focused on international trade and financial depth in Nigeria. The independent variables were total foreign trade, trade openness and bank loans to international traders while ratio of domestic credit to GDP was the dependent variable. Using econometric procedures i.e., unit root, Johansen cointegration and error correction model, we found that total trade increased financial depth but not significantly, trade openness decreased financial depth significantly while bank loans for international trade increased financial depth significantly. The conclusion was that international trade in Nigeria has not had the desired effect on the financial sector because of the non-significance of total trade while trade openness showed negative effect on financial depth in Nigeria. The recommendation was that Nigeria should intensify efforts towards achieving full productive economy so as to increase the country’s trade standings which will have positive effect on the trade financing functions of the financial sector.